RESPON PERTUMBUHAN DAN HASIL TANAMAN SAWI (Brassica rapa L.) DENGAN PEMBERIAN PUPUK ORGANIK CAIR DARI LIMBAH PASAR - Wajib Pandia (Universitas Quality, 2023)
The purpose of this study was to determine the growth response and yield of mustard greens (Brassica rapa L.) by administering liquid organic fertilizer and the right concentration to increase so as to get the best growth and best yields of mustard plants. This research was conducted in August 2022 in the village of Raya Village, Berastagi District, Karo Regency, North Sumatra Province, at an altitude of 1,300 asl. The method used in this study was an experimental method, with a simple randomized block design (RBD) consisting of 6 treatments and 4 repetitions, namely: (P0 = without POC (0 ml/l water), P1 = POC 5 ml/l water , P2 = POC 10 ml/l water, P3 = POC 20 ml/l water, P4= POC 30 ml/l water, P5= POC 40 ml/l water). The results showed that the application of liquid organic fertilizer with different concentrations had an effect on the parameters of plant height, number of leaves, leaf width, leaf length, average fresh weight and dry weight of mustard plants. Giving POC with a concentration of 40 ml/L of water gave the best results for mustard plants, namely producing plants with the highest wet weight compared to other treatments, namely 716.31 gr and dry weight, namely 53.31 gr